TANGGAPAN PEMBACA TERHADAP FAHRI (PERSPEKTIF RESEPSI SASTRA) - Munaris, Munaris (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
Literature receptive based research is a study which focuses on the readers, which is related to their perspective towards what they read. The objective of this research is to describe the readers? reception towards the character Fahri. To gain that objective, it is conducted a descriptive-kualitative-hermeunetics research. The source of data is taken form the reception text which is uploaded in the internet. The finding shows that (1) the readers recept Fahri through three dimensions: phyciological, psychological, and sociological; (2) some of the readers? receptions towards Fahri are negative, and the rest are positive; and (3) the readers are prone to recept Fahri from the dimensions of psychological, sociological, and phyciological. Most readers have positive perspective towards Fahri. This positiveness is expressed through some expression such as Fahri is smart, hard worker, and can be an imitated figure.